Black Soldier Fly Cultivation as Experiential Learning: A Mixed-Methods Study of Ecoliteracy and Circular Economy Education in an Indonesian Community Learning Center - Saripah, Iip; Erawan, Wahid; Irnawati, Hanifah; Dadang Yunus Lutfiansyah; Bariboon, Gumpanat (Journal of Nonformal Education, 2026)
Background – Organic waste management remains a major environmental challenge in Indonesia, requiring not only technological solutions but also educational approaches that promote environmental awareness and sustainable behavior. Black Soldier Fly (BSF) cultivation offers a practical approach that integrates organic waste management with environmental education and circular economy principles.Research Urgency – Despite growing interest in BSF cultivation for waste management, limited studies have explored its role as a learning medium for eco-literacy development and circular economy education, particularly in nonformal education settings.Research Objectives – This study aims to explore, through an exploratory mixed-methods case study, how BSF cultivation functioned as a learning strategy and experiential learning medium for eco-literacy development and circular economy education through the Maggotpreneur Program at PKBM Bhina Swakarya.Research Method – This study used an embedded mixed-methods case study design with a one-group pretest–posttest component, conducted over three weeks. Of 53 Package B and Package C learners initially assessed for experience and interest, 34 joined the training program, and the 14 who joined the BSF cultivation learning group (ages 14–45) and completed both pretest and posttest assessments formed the main analytic sample. Quantitative data (a 15-item knowledge test) were analyzed using paired-samples statistics and N-Gain scores; qualitative data from field observations and participant reflections were analyzed through iterative coding, categorization, and interpretation. Given the one-group design without a comparison group and the small sample, this study is exploratory in nature.Research Findings – Knowledge scores increased significantly from pretest to posttest, t(13) = 4.41, p < .001, with a mean N-Gain of 0.59 (moderate) and a large effect size (Cohen's d = 1.18), indicating a learning improvement in participants' understanding of organic waste management and circular economy concepts. Qualitative observations suggested increased environmental awareness and a shift in some participants' perceptions of organic waste, from viewing it as a disposal problem toward recognizing it as a resource with environmental and economic value.Research Conclusion – As an exploratory case study, this research provides preliminary evidence that BSF cultivation can serve as an experiential and contextual learning medium for promoting eco-literacy and circular economy education in nonformal education settings; confirmatory studies with comparison groups are needed to establish effectiveness.Research Novelty/Contribution – This study contributes by positioning BSF cultivation not only as an organic waste management practice but also as an experiential learning medium for eco-literacy development and circular economy education within a nonformal education context, specifically through the Maggotpreneur Program at a community learning center (PKBM) in Indonesia.